Self-perceived communicative competence and demotivation: a study of UiTM students / Hanis Kamarudin ... [et al.] - Kamarudin, Hanis; Abdul Malek, Nur Ain; Wan Mohamed, Wan Nazihah; Ayzan Ayub, Siti Ainul (UiTM Cawangan Kedah, 2021)
Scholars in language learning have recently taken an interest in self-perceived communicative competence (SPCC) and demotivation, albeit the relationship between these notions is rarely investigated. In Malaysia, many educators have encountered students who are unwilling to use their second language for communication and the reasons behind it could be determined by different demotivating factors. Thus, the association between the students' SPCC and demotivation was explored in this present study, specifically in the English language classes. A total of 250 diploma students of Universiti Teknologi MARA Cawangan Kelantan (UiTMCK) participated in the study in which the data were collected via SPCC and a demotivation questionnaire. Notably, SPCC was negatively associated with demotivation based on the Pearson Correlation Coefficient. The study's outcomes showed that as part of the effort to minimise the English as a Second Language (ESL) students' demotivation, educators are encouraged to develop the students' competency in communicating.